Training on the Use of Sharia Mobile Banking to Support Digital Financial Transactions - Bunga Andini; Paisal Paisal; Wahyu Febri Ramadhan Sudirman (Global Sustainability Research Institute, 2025)
The rapid development of digital technology has accelerated the transformation of banking services, including Islamic banking through the provision of mobile banking services. However, the utilization of Islamic mobile banking services among the community still faces several challenges, including limited digital literacy, inadequate understanding of service features, and low awareness of digital transaction security. This community service program aimed to enhance participants’ knowledge and skills in using Islamic mobile banking services to support digital financial transactions. The program was implemented through several stages, including preparation, educational sessions, demonstrations, hands-on practice, interactive discussions, and evaluation. The training materials covered the introduction of Islamic mobile banking services, digital transaction features, QRIS utilization, and digital transaction security awareness. The results indicated an improvement in participants’ understanding of Islamic mobile banking services, the benefits of digital financial transactions, and the importance of protecting personal data and banking accounts. Furthermore, participants demonstrated better practical skills in operating various mobile banking features independently. This program contributed to strengthening Islamic digital financial literacy and promoting the effective, secure, and sustainable use of digital banking services within the community.